THE INFLUENCE OF ORGANIZATIONAL CULTURE AND TRAINING ON ORGANIZATIONAL COMMITMENT AND ALSO ITS IMPLICATIONS ON THE PERFORMANCE OF HEALTH WORKERS IN PUSKESMAS JOHAR BARU DISTRICT - Suryadi, Handy; Aima, Muhammad Havidz (Dinasti Publisher, 2019)
The purpose of this research is to find out and explain the influence of organizational culture and training on organizational commitment and its implications for the performance of Puskesmas Johar Baru District employees. The research method uses a quantitative approach, which became the population in this research were 170 Health Center Staff Johar Baru District. The sample selection is done by simple random sampling technique (Slovin 5% error tolerance) so that as many as 120 respondents are determined. Data collection techniques using interviews and questionnaire instruments. The questionnaire survey instrument was randomly delivered to Johar Baru District's Puskesmas staff. Data were analyzed using structural equation modeling (SEM) with the Smart PLS software program version 3.2.8. This study revealed that organizational culture, training and organizational commitment had a significant positive effect on employee performance, both partially and simultaneously. In addition, organizational commitment mediates organizational culture and training on performance.